The Maillard reaction in foods and medicine - O'Brien, John, 1960 May 26-; ScienceDirect eBooks (Cambridge : Woodhead Publishing Ltd, 1998)
This collection of papers are devoted to a single chemical reaction, the Maillard reaction. They look at various different topics, such as its use in the food industry, and its relation to ageing and age-related diseases. This collection of papers are devoted to a single chemical reaction, the Maillard reaction. They look at various different topics, such as its use in the food industry, and its relation to ageing and age-related diseases.
Reaction mechanisms-- Food technology-- Kinetics and analytical aspects-- Flavour chemistry-- Toxilogical and antioxidants-- Health and disease.
Undergraduate.
ReferencesChapter 3. The Role of the Maillard Reaction in the Food Industry; Introduction; Chemistry of the Maillard Reaction; The Role of the Maillard Reaction in the Food Industry; Processes; Product Quality/Shelf Life; Industrial Examples; Conclusions; References; Chapter 4. Amadoriase Isoenzymes (Fructosyl Amine: Oxygen Oxidoreductase EC1.5.3) from Aspergillus fumigatus; Introduction; Materials and Methods; Results; Discussion; References; Part II:Reaction Mechanisms; Chapter 5. Correlations between Structure and Reactivity of Amadori Compounds: the Reactivity of Acyclic Forms; Introduction.
Elsevier
Keywords: Maillard reaction; Maillard reaction -- Congresses; TECHNOLOGY & ENGINEERING -- Food Science; Maillard reaction; Electronic books